The influence of energy migration on luminescence kinetics parameters in upconversion nanoparticles. (8th December 2016) - Alyatkin, Sergey; Asharchuk, Ilya; Khaydukov, Kirill; Nechaev, Andrey; Lebedev, Oleg; Vainer, Yuri; Semchishen, Vladimir; Khaydukov, Evgeny
Abstract: The mechanism of upconversion at the nanoscale is still under discussion. In this paper, we report on the experimental results of anti-Stokes luminescence kinetics in the upconversion nanoparticles of β -NaYF4 : 20%Yb 3+ ; 0.6%Tm 3+ . The parameters of the luminescence kinetics were found to be unambiguously dependent on the number of excitation quanta n, which are necessary for certain transitions between the energy states of thulium ions. The observed correlation has been explained by means of the long-lasting energy migration between the ytterbium ions. The spread in time between the luminescent maxima of the corresponding thulium transitions not only shows the nonlinear character of upconversion, but also reveals the time scale of energy migration as well. From these, we derive that the conventional Förster formalism applied to the estimation of energy transfer efficiency in UCNP-fluorophore pairs can provide misleading results.